Graphene-Based Electrochemical Sensor for Detection of Hepatocellular Carcinoma Markers - Liang, Ying; Xu, Yuan; Tong, Yaoyao; Chen, Yue; Chen, Xilu; Wu, Shimin (Frontiers in Chemistry, 2022)
Hepatocellular carcinoma (HCC) is a group of highly lethal malignant tumors that seriously threaten human health. The main way to improve the survival quality and reduce the mortality of HCC is early diagnosis and treatment. Therefore, it will be of great significance to explore new quantitative detection methods for HCC markers. With the rapid development of electrochemical biosensors and nanomaterials, electrochemical sensors based on graphene can detect tumor markers, with the advantages of simple operation, high detection sensitivity, and specificity. Combined with the published literature in recent years, the article briefly reviews the application of graphene-based electrochemical biosensors in the detection of HCC markers, including alpha-fetoprotein (AFP), Golgi protein-73 (GP73), exosomes, and microRNA-122 (miR-122).